1984
DOI: 10.1210/jcem-59-6-1224
|View full text |Cite
|
Sign up to set email alerts
|

A Primate Model of Human Postmenopausal Hot Flushes*

Abstract: The hot flush is the only symptom specifically attributable to the menopause. Hot flushes appear to represent an episodic derangement of thermoregulation as a result of estrogen deficiency but the underlying physiological mechanisms are unknown. We have developed an animal model for the study of hot flushes. Two female monkeys (Macaca arctoides) were trained to accept monitoring of scalp cutaneous temperatures. After baseline temperature recordings were obtained both monkeys were ovariectomized. A few days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 13 publications
5
11
0
1
Order By: Relevance
“…Irrespective of these mechanisms, our data show that estrogenic 3␣OH-tib and 3␤OH-tib are predominant in brain, including the hypothalamus, which is primarily involved in control of hot flushes (Stearns et al, 2002). This estrogenic metabolite pattern is in line with the observed estrogenic effects on the brain, i.e., a reduction in hot flushes as shown in ovariectomized monkeys (Jelinek et al, 1984) and postmenopausal women (Landgren et al, 2005). However, estrogenic effects of tibolone on the pituitary seem not to be very strong because tibolone only partly reduces follicle-stimulating hormone levels in postmenopausal women (Doeren et al, 2001) and cynomolgus monkeys (Gibbs et al, 2002), in contrast to continuous combined regimens resulting in near-complete suppression.…”
Section: Tissue Distribution Of Tibolone Metabolites In Monkeyssupporting
confidence: 79%
“…Irrespective of these mechanisms, our data show that estrogenic 3␣OH-tib and 3␤OH-tib are predominant in brain, including the hypothalamus, which is primarily involved in control of hot flushes (Stearns et al, 2002). This estrogenic metabolite pattern is in line with the observed estrogenic effects on the brain, i.e., a reduction in hot flushes as shown in ovariectomized monkeys (Jelinek et al, 1984) and postmenopausal women (Landgren et al, 2005). However, estrogenic effects of tibolone on the pituitary seem not to be very strong because tibolone only partly reduces follicle-stimulating hormone levels in postmenopausal women (Doeren et al, 2001) and cynomolgus monkeys (Gibbs et al, 2002), in contrast to continuous combined regimens resulting in near-complete suppression.…”
Section: Tissue Distribution Of Tibolone Metabolites In Monkeyssupporting
confidence: 79%
“…Previous studies have shown that tibolone is able to reduce hot flushes in cynomolgus monkeys in a similar way as ethinyl oestradiol (EE) [50] as shown in Fig. 3.…”
Section: Tibolone Metabolites and Relation To Hot Flush Reductionsupporting
confidence: 53%
“…Tibolone's tissue-selective action profile includes estrogenic action in brain and bone and no action in the uterus and the breast [Speroff, 1996;Kloosterboer, 2001]. Tibolone's effect on temperature regulation is not unexpected because it was shown to block hot flushes in a primate model [Jelinek et al, 1984]. Tamoxifen, another SERM with mixed activities, blocks tail skin temperature rise induced by morphine withdrawal when administered alone.…”
Section: Discussionmentioning
confidence: 99%